Reformasi Administrasi Pelayanan Publik di Kantor Camat Minas Kabupaten Siak Provinsi Riau - Eko Handrian; Siska Putriani (Universitas Muhammadiyah Mataram, 2021)
Reform is an effort to realize good governance. Bureaucratic reform provides hope for a more just and equitable service to achieve public welfare. This type of research is a descriptive survey research with quantitative methods where the data collection methods are Questionnaires, interviews, observations and documentation as a tool to study the data then the research data is used as raw material to analyze empirical conditions and the objectivity of the existence of research objectives at the research location. As for the results of the study, it is known that the Reform of Public Service Administration at the Siak District Head Office was implemented quite well. New Emphasis on Programs has built commitment and awareness by employees of the program, Changes in Attitudes and Behaviors of the Society and Members of the Bureaucracy are still low, public knowledge of program changes and there are still many people with low educational backgrounds, Changes in Leadership Style Leading to Open Communication and Participatory Management still not effective where the communication that is built is not direct communication but through the media and is limited by the bureaucratic structure, and the Efficient Use of Resources One of the problem points in reform is human resources, commitment and employee discipline that need to be built because of the limited impact resources. major changes in service at the Minas District Office of Siak Regency.